ANALISIS JAM MAKAN PADA DAUN TANAMAN SAWI HIJAU (Brassica rapa var. parachinensis L.) DENGAN TEKNIK PERUNUT RADIOAKTIF 32P - Nurfaizah, Nurfaizah; Sutapa, I Gst. Ngurah; Yuliara, I Made (BULETIN FISIKA; Vol 17 No 2 (2016): BULETIN FISIKA, 2016)
It has been conducted research on the analysis feeding hours of green cabbage leaves (Brassica rapa var. parachinensis L.) with a radioactive tracer technique 32 P . The feeding hour treatment plants conducted were at 07.00, 09:00, 11:00, 13:00 , 15:00 and 17:00 . The amount activity of Isotpe 32 P applied to 483 µCi/150 ml (168,542 x 10 3 Bq/ 150 ml) / plant, counting values activity of green cabbage leaves using Radiation Alert Inspector . Data activity was analyzed by ANOVA statistical analysis using SPSS 17.0 version, and Tukey's test with 95% significance result. Results of the analysis show that feeding hours (fertilization) of green cabbage leaves was the most effective at 09.00. Radioactive concentration at 09.00 was different to other hours treatments significantly.